Performance Indicators and Optimal Conditioning Duration in Endurance Horses Under Malaysian Conditions - Mohd Adzahan, Noraniza (2010)
The Malaysian endurance horses are not at their best level of performance due to improper conditioning techniques with inadequate or prolonged conditioning periods. As a consequence, unfit or fatigued horses participate in endurance races resulting in a high percentage of horses being eliminated due to lameness or metabolic ailments. There should be a reliable method for the screening of horses prior to endurance races to filter out the poor performers so that only good and qualified horses participate. There is also a need to determine the optimal conditioning period for producing horses at their best level of performance. Therefore, the objectives of the study were to characterize the Malaysian endurance horse population based on their performance levels and conditioning regimes, determine performance indicators for the identification of good and poor performance endurance horses and determine the optimal conditioning duration under Malaysian conditions for endurance horses to be at their best performance level. The usefulness of these performance indicators was tested by a field test, standardized endurance rides and in endurance races. A survey was conducted using a questionnaire to determine the total population of endurance horses in Peninsular Malaysia with regards to their performance and conditioning status. A 500 m standardized exercise test (SET) and standardized endurance rides (30 km track) of various distances were conducted before and during conditioning periods. Plasma samples obtained throughout SET as well as at pre- and post-exercise periods during the standardized endurance rides were analyzed for locate, cortisol, glucose, aspartate aminotransferase (AST), creatine kinase (CK) and electrolyte concentrations. These parameter were used to determine the performance indicators for the identification of good and poor performance endurance horses. Heart rates were also recorded by the heart rate monitor throughout the SET. A pair of SET was conducted at pre- and post-conditioning periods of the 1,2 and 3-month conditioning regimes to determine the optimal conditioning duration for producing the best conditioned horses. After undergoing these conditioning regimes the performances of the horses were evaluated in endurance races. Climatic factors (ambient temperature, relative humidity, and heat index) were analyzed to determine the diurnal changes and correlation between variables. In the 500 m SET, the mean V140 (velocity at a heart rate of 140 beat min-1), V200 (velocity at a heart rate of 200 beat min-1) and V LA4 (velocity at a blood lactate concentration of 4 mmol L-1) values for the highest performance horses were 10.65 ± 0.91, 19.08 ± 1.34 and 8.09 ± 1.07 m s-1, respectively, while for the lowest performance horses were 6.06 ± 0.67, 9.75 ± 1.34 and 6.08 ± 1.76 m s-1, respectively. The recovery heart rate and plasma lactate concentrations were 49 ± 8 beats min-1 and 6.0 ± 1.6 mmol L-1 respectively for the highest performing horses and 56 ± 3 beats min-1 and 8.6 ± 0.8 mmol L-1 respectively of the lowest. For the 30 km standardized endurance rides at velocities of 12 to 15 km hr-1, the parameters that could be used as the performance indicators were plasma lactate, cortisol, AST and CK concentration. The mean plasma cortisol, lactate, AST and CK concentrations were 1.9 ± 0.4 mmol L-1, 9.97 ± 1.98 µg dL-1, 321.7 ± 55.2 IU L-1 and 250 ± 39 IU L-1 respectively for the high and 3.5 ± 0.9 mmol L-1, 18.01 ± 4.22 µg dL-1, 471.6 ± 133.4 IU L-1 and 339 ± 63 IU L-1 respectively for the lowest performing horses. Based on the study, the 3-month conditioning duration showed the greatest increase in V140 (-1.95 ± 1.21 m s-1) and V200 (-3.75 ± 1.94 m s-1) compared to the 2-month (-1.69 ± 1.22 m s-1 and -3.5 ± 1.42 m s-1 respectively) and 1-month (-0.92 ± 0.69 m s-1 and -1.27 ± 0.94 m 2-1 respectively) conditioning durations. Conversely, the 2-month conditioning duration showed a greater increase in V LA2 (-2.93 ± 0.67 m s-1) and VLA4 (-2.16 ± 0.83 m s-1) than the 3-month (-1.42 ± 0.61 m s-1 and -1.01 ± 1.30 m s-1 respectively) condition duration. Ninety percent of horses subjected to the 2-month conditioning completed the regime, while only 60% of horses subjected to the 3-month conditioning completed the process. Parameters that can be used as performance indicator in the 500 m SET were V140, V200, VLA4, heart rates and plasma lactate concentrations after a 30 min recovery, and the plasma cortisol, glucose and AST concentrations at post-exercise periods. In the standardized 30 km endurance test ride, the best performance indicators were plasma cortisol, lactate, CK and AST concentrations. The study suggests that the optimal conditioning duration of endurance horses under Malaysian conditions is 2 month.